A computational multiscale model for anisotropic failure of sheet molding compound composites. (15th May 2022) - Görthofer, Johannes; Schneider, Matti; Hrymak, Andrew; Böhlke, Thomas
Abstract: We present a holistic multiscale approach for constructing anisotropic criteria describing the macroscopic failure of sheet molding compound composites based on full-field simulations of microscale damage evolution. We use an anisotropic damage model on the microscale that directly operates on the compliance tensor, captures matrix and bundle damage via dedicated stress-based damage criteria and allows for a comparison of simulation and experimental results. To identify the damage material-parameters used in the non-linear and time-consuming full-field simulations, we utilize Bayesian optimization with Gaussian processes. We validate the full-field predictions on the microscale and subsequently identify macroscopic failure criteria based on distributions taken from experimental findings. We propose failure surfaces in stress space and stiffness-reduction triggered failure surfaces to cover both a structural analysis and a design process perspective. Highlights: SMC composites show a macroscopic strain hardening behavior due to accumulation of damage on the microscale that eventually leads to abrupt failure. We utilize a modular and convex damage model in the framework of generalized standard materials that fulfills Wulfinghoff's damage growth criterion. We define specific extraction tensors motivated by Puck's laminate theory in combination with a pencil glide approach to account for maximum stress states, describing damage evolution in fiber bundles and matrix. We present a holistic multiscale approach for constructing anisotropic criteria describing the macroscopic failure based on microscale full-field damage evolution. Failure surfaces in stress space and stiffness-reduction triggered failure cover both a structural analysis and a design process perspective.